2013
DOI: 10.4238/2013.november.18.5
|View full text |Cite
|
Sign up to set email alerts
|

Construction of single-chain variable fragment antibodies against MCF-7 breast cancer cells

Abstract: ABSTRACT.A phage display library of single chain variable fragment (scFv) against MCF-7 breast cancer cells was constructed from C3A8 hybridoma cells. RNA from the C3A8 was isolated, cDNA was constructed, and variable heavy and light immunoglobulin chain gene region were amplified using PCR. The variable heavy and light chain gene regions were combined with flexible linker, linked to a pCANTAB 5E phagemid vector and electrophoresed into supE strain of Escherichia coli TG1 cells. Forty-eight clones demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Antibodies against classic biomarkers have been studied, and are still being analyzed in terms of biodistribution, their ability to penetrate tissue, toxicity, and efficient clearance. Some examples include scFvs directed against chondroitin sulfate (CS, abundant in the extracellular matrix in ovarian cancer) [ 94 ], CD24 (overexpressed in several tumors and in cancerous stem cells) [ 95 ], oncoprotein E6, expressed continuously in carcinomas associated with human papilloma virus type 16 (HPV 16) [ 96 ], gastrin receptor (CCK2R, playing a key role in the trigger and development of cancer) [ 97 ], dehydroepiandrosterone (DHEA, adrenocortical carcinoma marker) [ 98 ], against cancer cells overexpressing EGFR (epidermal growth factor receptor) [ 99 ], MCF-7 breast cancer cells [ 100 , 101 ], and SUM159 (breast cancer stem cells) [ 102 ]. They have all shown promising results.…”
Section: Applications Of Scfvsmentioning
confidence: 99%
“…Antibodies against classic biomarkers have been studied, and are still being analyzed in terms of biodistribution, their ability to penetrate tissue, toxicity, and efficient clearance. Some examples include scFvs directed against chondroitin sulfate (CS, abundant in the extracellular matrix in ovarian cancer) [ 94 ], CD24 (overexpressed in several tumors and in cancerous stem cells) [ 95 ], oncoprotein E6, expressed continuously in carcinomas associated with human papilloma virus type 16 (HPV 16) [ 96 ], gastrin receptor (CCK2R, playing a key role in the trigger and development of cancer) [ 97 ], dehydroepiandrosterone (DHEA, adrenocortical carcinoma marker) [ 98 ], against cancer cells overexpressing EGFR (epidermal growth factor receptor) [ 99 ], MCF-7 breast cancer cells [ 100 , 101 ], and SUM159 (breast cancer stem cells) [ 102 ]. They have all shown promising results.…”
Section: Applications Of Scfvsmentioning
confidence: 99%
“…To improve the immunogenicity of the DNA vaccines, we combined two different approaches: delivery of the DNA vaccine by electroporation and targeting the encoded antigen to a specialized dendritic cell subset (CD8α + ) using a single-chain antibody to the endocytic receptor DEC205 (scDEC). Previous studies revealed promising results using DNA vaccines that targeted antigens to dendritic cells against a variety of pathogens, including HIV [ 50 , 52 ], influenza [ 57 ], Yersinia pestis [ 58 ], P. yoelii [ 59 ], P. falciparum [ 47 ], T.cruzi [ 60 ], M. tuberculosis [ 61 ], T. gondii [ 62 ], dengue virus [ 55 ] and cancer [ 63 ]. This platform offers attractive advantages including stability, low cost of production, and the absence of the Fc domain [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an Fc domain eliminates potential interaction with Fc receptor‐expressing cells thereby improving not only specific targeting to DCs but also allowing for repeated immunizations without inducing deleterious host antibody responses . In prior studies our group and others have demonstrated the immunogenicity of scDEC‐targeted antigen after incorporation in both DNA and viral vectored vaccines . Here we prioritize scDEC‐protein vaccines because they offer a unique opportunity for scaling up strategies optimized with the parental anti‐DEC205 monoclonal antibody (αDECmAb)‐protein vaccines for eventual application in underdeveloped countries.…”
Section: Introductionmentioning
confidence: 99%